The Historical Context and Process of Founding Educational Sciences as an Academic Discipline in Iran - Rouhollah Shahabi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
In Iran, Educational Sciences began as an academic discipline in 1932, but, the essential questions here are, “what was the historical context of the establishment of educational sciences as a discipline in Iran?” and “what process did it go through to reach the stage of quantitative development?” It seems that the formation of educational sciences in Iran has taken place on the basis of historical factors including a) The Founding of Darul-Fonun, b) The Socio-cultural changes during the period between the founding of Dar ul-Fonun and the Persian Constitutional Revolution, c) The Persian Constitutional Revolution, and d) Sending of students to Europe. As a result of these, Educational Sciences in Iran was not rooted in traditional educational institutions and not rely on our legal and philosophical heritage. Educational sciences in Iran, were only able to emerge from the channel of professional provision (ie, teacher education) and to accept itself in our traditional society, perhaps if it had another path of emergence, it would have faced resistance. After emerging in such a context, Educational Sciences have undergone special historical periods to reach the stage of quantitative development that was discussed.